Temporal genetic structure of a stock of Prochilodus lineatus (Characiformes: Prochilodontidae) in the Mogi-Guaçu River ecosystem, São Paulo, Brazil - Da Rosa, Ivana F. [UNESP]; Deoliveira, Danielaj. [UNESP]; Dacruz, Vanessap. [UNESP]; Ashikaga, Fernandoy. [UNESP]; Costa, Gabrielaomura [UNESP]; Doretto, Lucasb. [UNESP]; Senhorini, Joséa.; Ritade, C. Rocha; Foresti, Fabiop. [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (FapUNIFESP (SciELO), 2022)
Prochilodus lineatus is a species of migratory fish widely distributed in the Paraná River basin, found mainly in the Grande, Pardo and Mogi-Guaçu rivers located in a well-developed region of the state of São Paulo. This study analyzes the genetic diversity and population structure in shoals of P. lineatus based on temporal analysis of specimens sampled over the years 2003, 2005, 2006, 2009, 2010, and 2015 in the Mogi-Guaçu River, São Paulo, at the region of Cachoeira de Emas. Genetic analysis performed using the D-Loop and seven microsatellite marker revealed significant genetic variability in all sampled groups. Moderate levels of structuring between groups were identified with the microsatellite markers (Fst = 0.14), while the mitochondrial marker did not reveal patterns of genetic structuring (Fst = 0.01). The genetic variability fluctuated over time, characterizing patterns of structuring among the analyzed samples. The occurrence of environmental alterations resulting in increased mortality rates, as well as changes in the water level in the ecosystem, among other factors, could determine changes in the reproductive behavior of species. The lack of favorable environmental conditions for reproduction in the basin, as reflected by tests of population bottlenecks, could have resulted in the differentiation of populations of P. lineatus over time.
Keywords: Curimbata; D-loop; Genetic diversity; Genetic structure; Microsatellites